Simulation study on thermal performance of novel phase change double skin facade - FU Yunchao; WU Zitong; ZHAO Yu; XIE Yumo; ZHAO Juan (Xi'an Gongcheng Daxue xuebao)
To address the issues of poor natural ventilation in double skin facades (DSF) and the excessive indoor temperature caused by solar radiation during summer, phase change material (PCM) is organically integrated into the DSF system, which proposes a novel phase change DSF. MATLAB numerical simulation software was employed to explore the PCM phase change time and the temperature rise in air ducts under different parameters. The results show that when the height of the phase change door increases from 2 m to 6m, the PCM phase change time is shortened, and the air outlet temperature slightly increases. Similarly, as the outdoor temperature rises from 10 ℃ to 30 ℃, the PCM phase change time decreases from 15.58 h to 12.92 h, while the air outlet temperature drops from 0.45 ℃ to 0.3 ℃. Additionally, when solar radiation increases from 200 W/m2 to 1 200 W/m2, the PCM phase change time significantly reduces from 35.15 h to 7.45 h, accompanied by an increase in air temperature at the outlet from 0.15 ℃ to 0.56 ℃. Variations in indoor temperature, ranging from 10 ℃ to 30 ℃, also lead to a reduction in PCM phase change time from 15.77 h to 13.62 h, with no significant impact on the air duct temperature.